A thousand years of productivity: the JRebel story. (22nd October 2012) - Kabanov, Jevgeni; Vene, Varmo
SUMMARY Millions of enterprises run web applications powered by the Java Enterprise Edition platform, but developing them is no small feat. Every UI change in development incurs a wait time of up to 15 min. JRebel is a tool that tackles the challenging problem of live application update for the Java Enterprise Edition platform. It does live code reloading, maps resources directly to the developer workspace, and propagates configuration changes to ensure that the developer can keep instantly alternating between the developing environment and the web browser, to save wasted time and increase the productivity flow. This paper describes our journey to build this product from the initial prototype to a major time saver for tens of thousands of users that it is today. We tried to document the most interesting issues and discoveries we made along the way and hope they will be of value to both the academical and industrial communities. Copyright © 2012 John Wiley & Sons, Ltd.